Novel insights into the role of the mobilome in ecological diversification and success of Staphylococcus haemolyticus as an opportunistic pathogen. Issue 1 (24th January 2022) - Saroha, Tanu; Chaudhry, Vasvi; Patil, Prabhu B.
Abstract : Staphylococcus haemolyticus is a species of coagulase-negative staphylococci that has primarily been studied as a human skin microbiome member and an emerging nosocomial pathogen. Here, we present the first complete genome of S. haemolyticus strains SE3.9, SE3.8 and SE2.14 reported as an endophyte of rice seed. Detailed investigation of the genome dynamics of strains from diverse origins revealed an expanded genome size in clinical isolates, and a role of many insertion sequence (IS) elements in strain diversification. Interestingly, several of the IS elements are also unique or enriched in a particular habitat. Comparative studies also revealed the potential movement of mobile elements from rice endophytic S. haemolyticus to strains from other pathogenic species such as Staphylococcus aureus . The study highlights the importance of ecological studies in the systematic understanding of genome plasticity and management of medically important Staphylococcus species.